Modified Newman and Friedman Extraoral Radiographic Technique - Saberi, Eshagali; Hafezi, Ladan; Farhadmolashahi, Narges; Mokhtari, Manoochehr (Iranian Endodontic Journal, 2012)
Introduction: Good radiographs are required for endodontic therapy and because some patient’s are intolerant to intraoral films and/or sensors, this can cause complications in endodontic treatment. Extraoral film placement can be used to obtain clinically diagnostic and working radiographs. Materials and Methods: The no. 2 receptor was placed against the model’s cheek and centered in the molar-premolar area. The central beam was directed toward this area from the opposite side. The vertical and horizontal angles that achieved the most accurate radiograph were calculated by trial and error. Results: The best method equated with the patient sitting upright and the Frankfort plane being horizontal to the floor and when the head was tilted 10 degrees toward the side being examined. For the upper posterior teeth the center of the image receptor was placed on the intersection of the ala-tragus and a parasagittal line while the upper border of receptor was parallel to the canthomeatal line; the cone was positioned a negative 25 degrees from the horizontal plane. The central beam was directed from midway between maxillary and mandibular premolars and molars of the opposite side. For the lower posterior teeth, the receptor was placed against the cheek on the side of interest and its lower border was parallel and 2 cm above the inferior border of the mandible. The cone was angled -20 degrees from the horizontal plane while the central beam was directed towards the mandibular molar-premolar region 1 cm below the lower border of the mandibular of the contralateral premolar/molar region. Conclusion: Using this novel technique, high quality images can be acquired for patients who cannot tolerate intraoral radiographs.